2016
DOI: 10.1007/s00264-016-3227-y
|View full text |Cite
|
Sign up to set email alerts
|

Survey study suggests that reverse total shoulder arthroplasty is becoming the treatment of choice for four-part fractures of the humeral head in the elderly

Abstract: Level III - Case controlled study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 28 publications
0
33
0
3
Order By: Relevance
“…Reverse total shoulder arthroplasty (TSA) was initially developed for treatment of cuff-tear arthropathy. In the last decade, there has been a shift toward reverse TSA as a primary operative solution for displaced proximal humeral fractures in the elderly, and it is now widely accepted as standard treatment 14 .…”
mentioning
confidence: 99%
“…Reverse total shoulder arthroplasty (TSA) was initially developed for treatment of cuff-tear arthropathy. In the last decade, there has been a shift toward reverse TSA as a primary operative solution for displaced proximal humeral fractures in the elderly, and it is now widely accepted as standard treatment 14 .…”
mentioning
confidence: 99%
“…In their recent systematic review and meta-analysis including level I-IV studies, Gallinet et al [16] , also concluded on the superiority of RSA, although they emphasized the lack of longterm studies. In a surgeon survey, Savin et al [31] report that most practitioners agree that RSA is at least as reliable as, and often more adapted than, HSA for managing four-part PHF in el-derly patients. One clear advantage of RSA over HSA is that, by granting full function to the deltoid muscle, RSA reduces the effect of poor or slow tuberosity healing on outcomes [16].…”
Section: Discussionmentioning
confidence: 99%
“…Research Center of Guangzhou University of Chinese Medicine, Guangzhou, Guangdong 510405, China. 3 Department of Joint Orthopaedic, the First A liated Hospital, Guangzhou University of Chinese Medicine, Guangzhou, Guangdong 510405, China. 4 The First A liated Hospital of Guangzhou University of Chinese Medicine.…”
Section: Consent For Publicationmentioning
confidence: 99%
“…Proximal humeral fracture (PHF) account for 4%~5% of all fractures, 26% of shoulder fractures [1]. It's concentrated in elder with osteoporosis and is the third most common in older patients, followed by femoral neck fractures and distal radius fractures [2,3]. We often use Neer classi cation criteria to assess the severity of this fracture injury.…”
Section: Introductionmentioning
confidence: 99%